Analisis Kepemimpinan Kepala Madrasah dalam Meningkatkan Disiplin dan Kinerja Guru di MAN 2 Kota Cilegon - Durotun Nasihah; Anis Fauzi; Hanafi Hanafi (Departement of Mathematics Education, 2023)
The purpose of this study was to determine the leadership of the head of the madrasah in improving teacher discipline and performance in MAN 2 Cilegon City. This research uses a qualitative approach. Data collection is carried out by means of interviews, observation, and documentation. The data obtained is then analyzed using qualitative data analysis consisting of: (a) data reduction, (b) data presentation, and (c) conclusions. The results of this study show that the leadership of the head of the madrasah in MAN 2 Cilegon City with a democratic leadership style that is open, communicative, and prioritizes common interests. Efforts made in improving discipline in MAN 2 Cilegon City are by cultivating commitment, reward and punishment, as well as using points for attendance. Meanwhile, the efforts of MAN 1 Cilegon City in improving teacher performance are by providing coaching, attending training and seminars, supervising. In general, the effectiveness of leadership in MAN 2 Cilegon City in improving teacher discipline and performance cannot be seen because it is still running, and the planned work programs are also still continuing from the previous leadership even though there are new programs implemented but all are still running. So the leadership of the head of the madrasah will affect in improving teacher discipline and performance, because the head of the madrasah is the spearhead in improving teacher discipline and performance.